Modelling of the nitrogen deposition and dietary lysine requirements of Redbro broilers - Santos, P. A. dos; Rabello, C. B. V.; Sakomura, N. K. [UNESP]; Silva, E. P. da [UNESP]; Dorigam, J. C. P. [UNESP]; Santos, M. J. B. dos; Lorena-Rezende, I. M. B. (Csiro Publishing, 2014)
The aim of this study was to determine the coefficients of the Goettingen model for Redbro birds and estimate the digestible lysine requirements. To determine the model parameters, three nitrogen balance trials were performed in Periods I (14-28 days), II (42-56 days) and III (70-84 days), using 42 birds per trial. The birds were individually housed and subjected to six diets with increasing levels of nitrogen, with lysine as the limiting amino acid (deficient by 20% in relation to other amino acids). Dietary nitrogen concentrations were 8, 16, 24, 32, 40 and 48 g/kg. A control diet was added to confirm lysine as the first limiting amino acid. Nitrogen balance trials were divided into 5 days of adaptation and two periods of excreta collection, each one of 5 days. The response of the birds to a control diet confirmed that lysine was the first limiting amino acid. The adjustment of the exponential functions between nitrogen retention or excretion and nitrogen intake allowed estimation of parameters of the Goettingen model. The maximum potential for nitrogen retention was 3276, 2585 and 2603 mg/BWkg0.67.day, nitrogen maintenance requirement was 225, 135 and 122 mg/BWkg0.67.day and efficiency of nitrogen utilisation was 313 x 10(-6), 406 x 10(-6) and 415 x 10(-6) in the phases of 14-28, 42-56 and 70-84 days. The digestible lysine intake for Periods I, II and III, based on 60% of the maximum potential for nitrogen retention, was 711, 989 and 1272 mg/day (1.225%, 1.137% and 1.09% of lysine in the diet for a daily feed intake of 58, 87 and 117 g/day), respectively.
Keywords: amino acid; genetic; metabolism; protein